Examination of the E-sports Attitudes of Individuals in Relation to Their Sporting Status and Individual Differences - TAPŞIN , Faik Orhun; ÖZDEMİR , Emin (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2024)
The objective of this study is to analyze individuals’ attitudes towards e-sports based on their engagement in sports activities and various variables. The study was conducted as a quantitative research, and the data was gathered through the snowball sampling method. The study utilized the esports attitude scale, developed by Savaş and Turan in 2023, as well as an information form designed by the researchers. The study involved a total of 211 participants. The data were analyzed using the SPSS 20.00 software package. Parametric tests were employed due to the normal distribution of the data. Pairwise comparisons were conducted using the T-test, while comparisons involving more than two groups were analyzed using the ANOVA test. If a significant difference was observed between the groups as determined by the ANOVA test, the Scheffe test was employed to identify the difference. The study analyzed participants’ attitudes towards e-sports by considering their total score as well as sub-dimensions, taking into account factors such as gender, age, daily internet usage time, and engagement in sports activities. There was no significant difference observed between the variables of gender and daily internet usage time and the total score and sub-dimensions of e-sports attitude. There was a significant difference in the overall score and specific aspects of e-sports attitude based on age. Upon analyzing the engaging in sports activity variable, a significant difference was observed in favor of individuals who engage in sports in the affective sub-dimension. According to the analyzed results, mean score of the affective subscale between individuals who engage in sports was as 23.01 and those who do not was as 21.96.